Chemical space of Escherichia coli dihydrofolate reductase inhibitors: New approaches for discovering novel drugs for old bugs. Issue 2 (7th September 2018) - Srinivasan*, Bharath; Tonddast‐Navaei, Sam; Roy, Ambrish; Zhou, Hongyi; Skolnick, Jeffrey
Abstract: Escherichia coli Dihydrofolate reductase is an important enzyme that is essential for the survival of the Gram‐negative microorganism. Inhibitors designed against this enzyme have demonstrated application as antibiotics. However, either because of poor bioavailability of the small‐molecules resulting from their inability to cross the double membrane in Gram‐negative bacteria or because the microorganism develops resistance to the antibiotics by mutating the DHFR target, discovery of new antibiotics against the enzyme is mandatory to overcome drug‐resistance. This review summarizes the field of DHFR inhibition with special focus on recent efforts to effectively interface computational and experimental efforts to discover novel classes of inhibitors that target allosteric and active‐sites in drug‐resistant variants of EcDHFR.